Assessment of Corneal Endothelial Cell Density in Patients with Dry Eye Disease - Saadat, Mishail; Muzaffar, Waqar; Perveen, Shagufta; Saleem, Muhammad Wasif; Bashir, Muhammad Babar; Malik, Zohaib Hassan (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare cell density of corneal endothelial cells in patients with dry eye disease versus controls. Study Design: Case-control study. Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from Jul to Dec 2024. Methodology: After permission of the ethical committee, the corneal topographic measurements of thirty-five patients with dry eyes (Group-A) were compared to age and gender matched controls (Group-B). The diagnosis of dry eye was established on tear break-up time (TBUT), Schirmer test and ocular surface disease index (OSDI) as part of comprehensive ophthalmic evaluation. Density of corneal endothelium, central corneal thickness and hexagonality of cells was recorded and compared between groups along with demographics. Results: The primary outcome was endothelial cell density of cornea. The corneal endothelial cell density in Group-A patients was 2294.94±242.03 cells per mm2 and corneal endothelial density in Group-B patients was 2949.62±375.8 cells per mm2 (p<0.001). The central corneal thickness was 517.80±6.30 um in Group-A and 544.88±16.76 um in Group-B (p<0.001). The epithelial cell hexagonality was 64.17±9.90 in Group-A and 68.77±4.80 in Group-B (p=0.017). Conclusion: We concluded that patients with dry eyes have reduced density of corneal endothelial cells along with reduced central thickness of cornea, cell hexagonality and best corrected visual acuity.